2017
DOI: 10.1128/jvi.01653-16
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Promotes Antiviral Humoral Immunity by Differentially Regulating CD4 Helper T Cell and B Cell Responses

Abstract: mTOR has important roles in regulation of both innate and adaptive immunity, but whether and how mTOR modulates humoral immune responses have yet to be fully understood. To address this issue, we examined the effects of rapamycin, a specific inhibitor of mTOR, on B cell and CD4 T cell responses during acute infection with lymphocytic choriomeningitis virus. Rapamycin treatment resulted in suppression of virus-specific B cell responses by inhibiting proliferation of germinal center (GC) B cells. In contrast, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 40 publications
6
40
0
Order By: Relevance
“…This effect was dependent on virus priming and of CD4 + but not CD8 + T cells . Another experimental model showed that sirolimus interferes with mTOR activity altering the balance between Th1 and follicular T helper cells differentiation and specifically inhibiting B‐cell responses during primary lymphocytic choriomeningitis virus infection and protein immunization induced by B‐cell receptor antigen stimulation . Whether the observed trend toward lower recurrence rate is associated with mTOR inhibitor associated expansion of newly formed CMV‐specific CD8 + T cell clones and/or altered B‐cell response is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This effect was dependent on virus priming and of CD4 + but not CD8 + T cells . Another experimental model showed that sirolimus interferes with mTOR activity altering the balance between Th1 and follicular T helper cells differentiation and specifically inhibiting B‐cell responses during primary lymphocytic choriomeningitis virus infection and protein immunization induced by B‐cell receptor antigen stimulation . Whether the observed trend toward lower recurrence rate is associated with mTOR inhibitor associated expansion of newly formed CMV‐specific CD8 + T cell clones and/or altered B‐cell response is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The centre of B‐cell responses is the GC reaction, in which Tfh–GCB cell interactions are essential . Recently, the regulatory role of mTOR in Tfh–GCB cell interactions was clearly dissected . In fact, inactivation of mTORC1 signalling by rapamycin led to a halt of GCB cell responses and impaired helper CD4 T‐cell differentiation during viral infection .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the regulatory role of mTOR in Tfh–GCB cell interactions was clearly dissected . In fact, inactivation of mTORC1 signalling by rapamycin led to a halt of GCB cell responses and impaired helper CD4 T‐cell differentiation during viral infection . More recently, Tfh‐intrinsic mTOR signalling was shown to support Tfh cell differentiation and function by re‐modulating metabolism and promoting proliferation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although typically used as an immuno‐suppressant to prevent allograft rejection in transplant patients, rapamycin administration during T‐cell priming or expansion following vaccination can enhance T CM development . This strategy, while beneficial for vaccinations requiring T CM development, may be detrimental in vaccinations attempting to enhance T RM development or humoral immunity, both of which can be negatively impacted upon by rapamycin administration . So while there is great potential for manipulating memory T‐cell metabolism to improve human health, the key to successful therapies will be to further understand the biology of immune cell metabolism and to develop creative ways to deliver therapies in a targeted manner.…”
Section: Therapeutic Opportunities For Targeting Memory T‐cell Metabomentioning
confidence: 99%